Molecular Mechanisms of Lysosome and Nucleus Communication. Issue 11 (November 2020) - Zhao, Qian; Gao, Shihong Max; Wang, Meng C.
Abstract : Lysosomes transcend the role of degradation stations, acting as key nodes for interorganelle crosstalk and signal transduction. Lysosomes communicate with the nucleus through physical proximity and functional interaction. In response to external and internal stimuli, lysosomes actively adjust their distribution between peripheral and perinuclear regions and modulate lysosome–nucleus signaling pathways; in turn, the nucleus fine-tunes lysosomal biogenesis and functions through transcriptional controls. Changes in coordination between these two essential organelles are associated with metabolic disorders, neurodegenerative diseases, and aging. In this review, we address recent advances in lysosome–nucleus communication by multi-tiered regulatory mechanisms and discuss how these regulations couple metabolic inputs with organellar motility, cellular signaling, and transcriptional network. Highlights: Lysosomal–nuclear communication coordinates lysosomal positioning, metabolism, and signaling with nuclear transcription to support fundamental cellular activities. Lysosomal positioning between peripheral and perinuclear regions is subject to cooperative regulation in response to metabolic stimuli and contributes to lysosomal functions and signaling. Retrograde transport of chaperone proteins and transcription factors from the lysosome to the nucleus is actively regulated by metabolic signaling. Nuclear transcriptional networks comprise a variety of different transcription factors that act independently or coordinately to fine tune lysosomal-autophagic gene expression.